RHETORICAL COMPETENCE AS A BASIS FOR THE FORMATION OF PROFESSIONAL COMMUNICATION IN THE CONDITIONS OF DIGITALIZATION (Scientific journal of the Fergana State University, 2025)
The article examines the role of rhetorical competence as a key component in the formation of professional communication in the context of digitalization. The influence of digital technologies on the nature of business communication and the requirements for rhetorical skills in the professional environment are analyzed. The features of rhetorical competence in online communication, including virtual meetings, business correspondence and interaction in social networks are studied. The main methods and approaches that contribute to the development of rhetorical skills necessary for effective professional communication in the context of remote work and rapid information exchange are determined. A conclusion is made about the importance of rhetorical competence as a factor contributing to increased trust, the establishment of positive relationships and the effectiveness of interaction in the digital professional environment.